Preparation process of green and environment-friendly nano photonic crystal synthetic leather with rich appearance
By applying nanophoton crystal film and composite process in leather materials, the environmental protection and functional limitations of traditional leather are solved, and a green and environmentally friendly nanophoton crystal synthetic leather that is wear-resistant, stain-resistant and multi-colored is achieved to meet the needs of high-end fashion fields.
Patent Information
- Application Number
- CN202510337242.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-07-29
AI Technical Summary
Traditional leather dyeing and coating processes have insufficient environmental protection, apparent singularity and functional limitations, resulting in environmental pollution and chemical residue risks, and cannot meet the needs of high-performance and multifunctional leather materials.
The nanophoton crystal film is used as the substrate layer, and by scraping the multi-layer slurry and combining with the pasting process, an apparently rich green and environmentally friendly nanophoton crystal synthetic leather is formed. The optical properties of the nanophoton crystal film are combined with the flexibility and wear resistance of the leather to achieve a unique gloss and color effect.
It improves the environmental protection, functionality and apparent richness of synthetic leather, has wear resistance, stain resistance and diverse color changes, conforms to environmental protection concepts, and is suitable for high-end fashion fields.
Smart Images

Figure CN120382703A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of leather materials, and particularly relates to a preparation process of a nano-photonic crystal synthetic leather with rich appearance and green environmental protection.
Background Art
[0002] With the continuous improvement of people's requirements for the quality and functions of leather products, we have been seeking product innovation to enhance competitiveness and added value. Traditional leather dyeing and finishing processes may use a large amount of chemical dyes to penetrate the fiber structure for coloring, and auxiliaries such as heavy metal complexing agents and fixing agents need to be used, which easily leads to the risk of wastewater pollution and chemical residues, and also causes certain pollution to the environment.
[0003] The color of the nano-photonic crystal film originates from the modulation of light by the physical structure, and has the characteristics of non-toxic and environmental protection, meeting the current environmental protection concept and the requirements of sustainable development. The nano-photonic crystal film has unique optical properties. Based on the periodic dielectric structure, it produces Bragg diffraction on light, and can generate a variety of colors by precisely controlling the structural parameters, with high color purity and strong angle dependence. It is widely used in the fields of display, sensing, anti-counterfeiting, etc., providing an optical technology basis for the invention of nano-photonic crystal synthetic leather. The continuous development of material composite technology also makes it possible to composite the nano-photonic crystal film with leather.
[0004] In view of this, the inventor of this case has conducted in-depth research on the above problems, and thus this case has been produced.
Summary of the Invention
[0005] The present invention aims to solve the technical problems of insufficient environmental protection, single appearance, and limited functions of traditional synthetic leather, and provides a preparation process of a nano-photonic crystal synthetic leather with rich appearance and green environmental protection, seeking product innovation to enhance competitiveness, and improving the appearance richness, environmental protection, and functionality of the synthetic leather.
[0006] The present invention is implemented as follows: A preparation process of a nano-photonic crystal synthetic leather with rich appearance and green environmental protection includes a first process step: selecting a nano-photonic crystal film as the first base layer; scraping and coating a surface layer slurry on the nano-photonic crystal film, and completely drying it to form a surface layer slurry layer; scraping and coating a middle layer slurry on the surface layer slurry layer, and completely drying it to form a middle layer slurry layer; scraping and coating a bottom layer slurry on the middle layer slurry layer, drying it to a semi-dry state to form a bottom layer slurry layer; laminating a base layer on the bottom layer slurry layer; and then performing drying, cooling, peeling, trimming, and winding to obtain a semi-finished product of the first process.
[0007] Further, the surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; when the surface layer slurry is scrape-coated on the nano-photonic crystal film, the number of coating rods is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the auxiliary agent until there is no peculiar smell; the middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; when the middle layer slurry is scrape-coated on the surface layer slurry layer, the number of coating rods is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry; the bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 8000 - 10000 CPS; when the bottom layer slurry is scrape-coated on the middle layer slurry layer, the number of coating rods is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 7 - 10 s to dry to a semi-dry state, and it can form a clear fingerprint mark when pressed with a finger to form the bottom layer slurry layer.
[0008] Further, the thickness of the bass layer is 1.15 - 1.25 mm.
[0009] Further, a PET layer is adhered to the side of the nano-photonic crystal film away from the surface layer slurry layer. The PET layer serves as a carrier for the nano-photonic crystal film when scraping the surface layer slurry, and the PET layer is peeled off from the nano-photonic crystal film during the peeling step.
[0010] Further, it also includes a second manufacturing process step: Select a release paper as the second base material layer; scrape and dry a fabric slurry on the release paper to form a fabric slurry layer; scrape and dry a bottom slurry on the fabric slurry layer to a semi-dry state to form a bottom slurry layer, obtaining a semi-finished product of the second manufacturing process.
[0011] Further, the fabric sizing agent is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. When the fabric sizing agent is scraped and coated on the release paper, the number of coating bars is 15 filaments. It is placed in an oven and dried at temperatures of 60°C, 75°C, 90°C, 100°C, 90°C, 75°C, and 60°C, and the vehicle speed is set at 13 m / min. The base sizing agent is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of crosslinking agent. When the base sizing agent is scraped and coated on the fabric sizing agent layer, the number of coating bars is 18 filaments, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110°C, and the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 7 - 10 s until it is in a semi-dry state, and there are some fingerprint marks when pressed with a finger to form a base sizing agent layer.
[0012] Further, the release paper serves as the carrier of the fabric sizing agent layer, and the release paper can be any one of a mirror release paper or a matte suede release paper.
[0013] Further, it also includes a laminating process step: the base sizing agent layer of the semi-finished product of the second process is laminated with the nano-photonic crystal film of the semi-finished product of the first process using a laminating machine; then it is dried, cooled and shaped, the release paper is peeled off, trimmed, and wound up to obtain a nano-photonic crystal synthetic leather.
[0014] Further, first apply a layer of water above the nano-photonic crystal film and then perform the laminating operation with the base sizing agent layer; the drying in the laminating process step is carried out at a temperature of 140°C with a vehicle speed of 6 m / min, and the drying duration is 7 - 10 min.
[0015] Further, the nano-photonic crystal synthetic leather includes, from top to bottom, a fabric sizing agent layer, a base sizing agent layer, a nano-photonic crystal film layer, a surface sizing agent layer, a middle sizing agent layer, a bottom sizing agent layer, and a base layer.
[0016] The preparation process of a nano-photonic crystal synthetic leather of the present invention works synergistically through three steps: the first process, the second process, and the laminating process; the first process provides basic optical properties, abrasion resistance, and stain resistance, endowing the synthetic leather with core functions; the second process introduces diverse surface textures through different release papers (mirror / matte) to enrich the apparent layering; the laminating process combines the optical properties of the first process with the textures of the second process to achieve a composite effect of "physical structural color + texture design", making the nano-photonic crystal synthetic leather have the advantages of diverse apparent effects achieved by the superposition of structural color and texture, being green and environmentally friendly, and significantly improving the abrasion resistance and peel strength.
Description of the Drawings
[0017] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0018] Figure 1 It is a schematic structural diagram of the semi-finished product of the first process in the present invention.
[0019] Figure 2 It is a schematic structural diagram of the semi-finished product of the second process in the present invention.
[0020] Figure 3 It is an exploded view of the surface-rich, green and environmentally friendly nano-photonic crystal synthetic leather in the present invention.
[0021] Figure 4 It is a schematic structural diagram of the surface-rich, green and environmentally friendly nano-photonic crystal synthetic leather in the present invention.
[0022] Reference numerals:
[0023] Semi-finished product of the first process 100, semi-finished product of the second process 200, fabric slurry layer 1, bottom slurry layer 2, nano-photonic crystal film 31, PET layer 32, surface layer slurry layer 4, middle layer slurry layer 5, bottom layer slurry layer 6, base layer 7, release paper 8.
Specific Embodiments
[0024] In order to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings of the specification and specific embodiments.
[0025] Refer to the attached Figure 4 As shown, in the present invention, a nano-photonic crystal synthetic leather is further provided, which sequentially includes a fabric slurry layer 1, a bottom slurry layer 2, a nano-photonic crystal film 31, a surface layer slurry layer 4, a middle layer slurry layer 5, a bottom layer slurry layer 6, and a base layer 7 from top to bottom.
[0026] The nanophotonic crystal synthetic leather of the present invention utilizes a nanophotonic crystal film 31 as a composite carrier, fully demonstrating the advantages of the nanophotonic crystal film 31 on the leather material, resulting in significant improvements in both appearance and performance. All test results meet or exceed the required standards, creating a new approach and new effects for the appearance of synthetic leather. The nanophotonic crystal synthetic leather exhibits three key performance improvements: Improved wear resistance: The nanophotonic crystal film 31 imparts excellent wear resistance to the synthetic leather, significantly improving its surface hardness compared to traditional leather. This significantly reduces scratches and wear during long-term use, significantly extending the service life of the synthetic leather product. Enhanced optical performance: The nanophotonic crystal film 31, with its unique optical properties, imparts unique luster and color effects to the synthetic leather, such as metallic luster and color-changing effects. This enhances the aesthetics and stylishness of the synthetic leather product, meeting the stringent requirements for leather appearance in the high-end fashion sector. Improved stain resistance: The dense structure of the nanophotonic crystal film 31 makes the synthetic leather surface less susceptible to stains and easier to clean, facilitating the daily maintenance and care of the leather product.
[0027] Reference Attachment Figures 1-4 As shown, the present invention also provides a preparation process for an apparently rich, green and environmentally friendly nanophotonic crystal synthetic leather, comprising a first process step: selecting a nanophotonic crystal film 31 as a first substrate layer; applying a surface slurry on the nanophotonic crystal film, and completely drying it to form a surface slurry layer 4; applying a middle slurry on the surface slurry layer 4, and completely drying it to form a middle slurry layer 5; applying a bottom slurry on the middle slurry layer 5, and drying it to a semi-dry state to form a bottom slurry layer 6; pressing a base layer 7 on the bottom slurry layer 6; and then drying, cooling, peeling, trimming, and rolling up to obtain a first process semi-finished product 100.
[0028] The present invention pioneered the application of nanophotonic crystal film in the preparation process of synthetic leather, combining the optical properties of nanophotonic crystal film with the excellent properties of leather such as flexibility and wear resistance, so that the surface of synthetic leather has a strong luster, strong and obvious color changes under different angles and light, and has gorgeous color change characteristics, giving leather new functions and values, and meeting the needs of different fields for high-performance and multifunctional leather materials; because the color of the nanophotonic crystal film comes from the modulation of light by the physical structure, it is non-toxic and environmentally friendly, in line with current environmental protection concepts and sustainable development requirements, and provides a new direction for the green development of the leather industry.
[0029] In the present invention, the nano-photonic crystal film 31 is a structural color film with high hardness and optical properties based on the 3D ordered arrangement of ppo nano-photonic crystals with nano-microspheres. The nano-photonic crystal film 31 has three characteristics: a PVC or TPU film with PPO, providing a unique structural color; the structural color does not fade over time; the color changes with the incident light direction or viewing angle.
[0030] Preferably, the nano-photonic crystal film 31 is selected from a series of nano-photonic crystal films produced by Guangdong Zhuhai Guangyu Technology Co., Ltd. (Model: PP0-E; Film physical properties: film thickness 15nm, stretchability ≥ 100, visible light transmittance 85%, haze ≤ 5). The material is a fully transparent organic polymer material. It forms a sheet-like pigment through the ordered arrangement structure of nano-microspheres, and realizes multiple color effects by Bragg diffraction, making the pigment have excellent transparency, high chroma, and elegant texture. Moreover, no colorant is added, it does not contain chemical dyes, is non-toxic and pollution-free, and has good stretching and pressing physical properties.
[0031] In the first process step, the surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS. The solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When the surface layer slurry is scrape-coated on the nano-photonic crystal film 31, the number of coating bars is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no odor.
[0032] In the first process step, the middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; when the middle layer slurry is scrape-coated on the surface layer slurry layer 4, the number of coating bars is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry.
[0033] In the first manufacturing step, the bottom slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 8000 - 10000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500. When the bottom slurry is scrape-coated on the middle slurry layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, the drying air volume is 160 cm3 / min for uniform blowing, the drying time is 7 - 10 s, and it is dried to a semi-dry state, and a clear fingerprint mark can be formed by pressing with a finger, thus forming the bottom slurry layer 6.
[0034] In the first manufacturing step, the thickness of the bass layer 7 is 1.15 - 1.25 mm, and it has good flexibility and peeling performance.
[0035] In the first manufacturing step, a PET layer 32 is attached to the side of the nano-photonic crystal film 31 away from the surface slurry layer 4. When scraping the surface slurry, the PET layer 32 serves as a carrier for the nano-photonic crystal film 31, and the PET layer 32 is peeled off from the nano-photonic crystal film 31 during the peeling step. The PET layer 32 serves as a carrier for the nano-photonic crystal film 31 and plays an excellent protective role with its good transparency, gloss, peelability, moisture resistance, and airtightness, preventing damage to the nano-photonic crystal film 31 due to external forces during transportation or use.
[0036] In order to produce the best first manufacturing semi-finished product 100 in the first manufacturing process, control experiments are carried out through the following three schemes, and the best first manufacturing semi-finished product 100 is selected according to the test data.
[0037] Scheme 1
[0038] First manufacturing step: Select a nano-photonic crystal film as the first base layer; scrape the surface slurry on the nano-photonic crystal film and completely dry it to form the surface slurry layer 4; scrape the middle slurry on the surface slurry layer 4 and completely dry it to form the middle slurry layer 5; scrape the bottom slurry on the middle slurry layer 5 and dry it to a semi-dry state to form the bottom slurry layer 6; press the bass layer 7 on the bottom slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the bass layer 7 is 1.15 - 1.25 mm; then at a temperature of 100 - 110 °C, dry, cool and shape, peel the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain the first manufacturing semi-finished product 100.
[0039] The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 40.0 ± 2.0%, the breaking strength is ≥ 30.0, and the elongation at break is ≥ 500; when the surface layer slurry is knife-coated on the nano - photonic crystal film, the number of coating bars is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell.
[0040] The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 40.0 ± 2.0%, the breaking strength is ≥ 30.0, and the elongation at break is ≥ 500; when the middle layer slurry is knife-coated on the surface layer slurry layer 4, the number of coating bars is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry.
[0041] The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 8000 - 10000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500; when the bottom layer slurry is knife-coated on the middle layer slurry layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, and the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 7 - 10 s until it is semi - dry, and a clear fingerprint can be formed when pressed with a finger to form the bottom layer slurry layer 6.
[0042] Scheme Two
[0043] The first manufacturing step: Select a nano - photonic crystal film as the first base layer; scrape and coat a surface layer slurry on the nano - photonic crystal film, and completely dry it to form a surface layer slurry layer 4; scrape and coat a middle layer slurry on the surface layer slurry layer 4, and completely dry it to form a middle layer slurry layer 5; scrape and coat a bottom layer slurry on the middle layer slurry layer 5, and bake it to a semi - dry state to form a bottom layer slurry layer 6; press a bass layer 7 on the bottom layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the bass layer 7 is 1.15 - 1.25 mm; then, at a temperature of 100 - 110 °C, dry, cool and shape, peel the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain a semi - finished product 100 of the first manufacturing process.
[0044] The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 40.0 ± 1.0%, the breaking strength is ≥30.0, and the elongation at break is ≥300; when scraping and coating the surface layer slurry on the nano - photonic crystal film, the number of coating rods is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell.
[0045] The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 40.0 ± 1.0%, the breaking strength is ≥30.0, and the elongation at break is ≥300; when scraping and coating the middle layer slurry on the surface layer slurry layer 4, the number of coating rods is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry.
[0046] The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 8000 - 10000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥20.0, and the elongation at break is ≥500; when scraping and coating the bottom layer slurry on the middle layer slurry layer 5, the number of coating rods is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, and the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 7 - 10 s to bake it to a semi - dry state, and a clear fingerprint can be formed when pressed with a finger, thus forming a bottom layer slurry layer 6.
[0047] Solution Three
[0048] The first manufacturing step: Select a nano - photonic crystal film as the first base layer; scrape a surface layer slurry on the nano - photonic crystal film and completely dry it to form a surface layer slurry layer 4; scrape a middle layer slurry on the surface layer slurry layer 4 and completely dry it to form a middle layer slurry layer 5; scrape a bottom layer slurry on the middle layer slurry layer 5 and bake it to a semi - dry state to form a bottom layer slurry layer 6; press a bass layer 7 on the bottom layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the bass layer 7 is 1.15 - 1.25 mm; then, at a temperature of 100 - 110 °C, dry, cool and shape, peel the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain a semi - finished product 100 of the first manufacturing process.
[0049] The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥40.0, and the elongation at break is ≥650. When scraping the surface layer slurry on the nano - photonic crystal film, the number of coating rods is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell.
[0050] The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥40.0, and the elongation at break is ≥650. When scraping the middle layer slurry on the surface layer slurry layer 4, the number of coating rods is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry.
[0051] The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 8000 - 10000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥20.0, and the elongation at break is ≥500; when scraping the bottom layer slurry on the middle layer slurry layer 5, the number of coating rods is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, and the drying air volume is 160 cm 3Blow air evenly at / min, with a drying time of 7 - 10 s until it reaches a semi - dry state, where a clear fingerprint can be formed when pressed with a finger, thus forming the bottom slurry layer 6.
[0052] Comparison of test results for Schemes One to Three in Table 1
[0053]
[0054]
[0055] Comparative analysis of the test results of the three schemes (in the three schemes, the parameters of polyurethane resin A are different):
[0056] 1. In the Taber abrasion resistance test, all three schemes met the basic requirements (200 revolutions), and the result ranking was Scheme Three > Scheme Two > Scheme One. In the Stoll abrasion resistance test, all three schemes met the basic requirements (1000 times), and the result ranking was Scheme Three > Scheme Two > Scheme One. In the yellowing resistance test, all three schemes met the basic requirements (grade 4 - 5), and the result ranking was Scheme Two > Scheme Three > Scheme One. In the folding resistance test, the tests at room temperature for all three schemes were qualified, but only Scheme One was unqualified in the low - temperature folding resistance test (-15°C), and the other schemes were qualified. In the peel strength test, the values of all three schemes were greater than 105, and all were qualified. The result ranking was Scheme Three > Scheme Two > Scheme One.
[0057] 2. The apparent effect of Scheme One has poor gloss, and the abrasion resistance, yellowing resistance, and low - temperature folding resistance results are poor; the apparent effect of Scheme Two has slightly better gloss, and the abrasion resistance, yellowing resistance, and folding resistance at normal and low temperatures are better, but the peel strength and abrasion resistance performance are less than those of Scheme Three; the apparent effect of Scheme Three has the best gloss, and the abrasion resistance, yellowing resistance, folding resistance at normal and low temperatures, and peel strength all show excellent performance.
[0058] Through comprehensive evaluation of the test results and the apparent effect, it is concluded that Scheme Three not only has the best gloss in the apparent effect but also has the best results in all tests.
[0059] In order to enrich the apparent effect of the synthetic leather, a compound lamination is carried out to achieve the presentation effect of crystal films with various patterns. The preparation process of the environmentally friendly nano - photonic crystal synthetic leather with rich apparent effect of the present invention further includes a second process step: selecting the release paper 8 as the second substrate layer; scraping and coating the fabric slurry on the release paper 8 and drying it to form the fabric slurry layer 1; scraping and coating the bottom slurry on the fabric slurry layer 1 and drying it to a semi - dry state to form the bottom slurry layer 2, thus obtaining the second - process semi - finished product 200.
[0060] In the second process step, the fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. The solid content of the polyurethane resin C is 30.0±1.0, the modulus is 70.0±2.0%, the breaking strength is ≥40.0, and the breaking elongation is ≥650. When the fabric slurry is coated on the release paper 8, the number of coating rods is 15, and it is placed in an oven and dried at temperatures of 60°C, 75°C, 90°C, 100°C, 90°C, 75°C, and 60°C. The vehicle speed is set to 13m / min.
[0061] In the second process step, the primer slurry is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of a bridging agent. The polyurethane resin D has a solid content of 70.0±2.0%, a modulus of 4.0±1.0, a breaking strength ≥30.0, and an elongation at break ≥500. When the primer slurry is applied to the fabric slurry layer 1, the number of coating rods is 18, the coating amount is controlled at 200-220g / m2, the drying temperature is controlled at 100-110°C, and the drying air volume is 160cm 3 / min uniform air blowing, drying time is 7-10s, drying to a partially dry state, pressing with a finger to leave a slight fingerprint, forming the primer slurry layer 2. The bridging agent N-75 bridging agent is an aliphatic polyisocyanate (hexamethylene diisocyanate biuret), present in the form of about 75% butyl acetate (EAC) solution, and the appearance is a colorless to slightly yellow transparent liquid.
[0062] In the second process step, the release paper 8 serves as a carrier for the fabric slurry layer 1. The release paper 8 has a textured feel and can be either a mirror-finished release paper 8 or a matte-finished velvet-finished release paper 8. The first-process semi-finished product 100 obtained in the first process utilizes a nanophotonic crystal film, exhibiting a strong gloss and vibrant colors, often with a mirror-finished, flat texture. The lamination process is designed to impart a richer texture and presentation to the first-process semi-finished product 100. If the second process uses mirror release paper 8, the surface of the obtained nanophotonic crystal synthetic leather not only has the texture effect of the release paper 8 but also has the optical color of the nanophotonic crystal film, so that the product has a variety of textures without losing the unique color effect of the photonic crystal film; if the second process uses matte velvet release paper 8, the surface of the obtained nanophotonic crystal synthetic leather will form a layer of matte velvet effect, which makes the product more layered, looks more low-key and luxurious, appears more natural and soft, the leather surface is more delicate, and feels soft and smooth, providing a better tactile experience.
[0063] The preparation process of the visually rich, green and environmentally friendly nano - photonic crystal synthetic leather of the present invention further includes a laminating process step: using a laminating machine to perform a face - laminating operation on the base - material slurry layer 2 of the second - process semi - finished product 200 and the nano - photonic crystal film 31 of the first - process semi - finished product 100; then drying, cooling and shaping, peeling off the release paper 8, trimming, and winding to obtain the nano - photonic crystal synthetic leather. In the laminating process step, first apply a layer of water above the nano - photonic crystal film 31, and then perform the face - laminating operation with the base - material slurry layer 2; the drying in the laminating process step is carried out at a temperature of 140 °C, with a vehicle speed of 6 m / min for drying, and the drying duration is 7 - 10 min.
[0064] The following are several examples and comparative examples used to illustrate the beneficial technical effects of the preparation process of the nano - photonic crystal synthetic leather of the present invention.
[0065] Example 1
[0066] A preparation process of a visually rich, green and environmentally friendly nano - photonic crystal synthetic leather:
[0067] The first - process steps: Select a nano - photonic crystal film as the first base layer; scrape a surface - layer slurry on the nano - photonic crystal film and completely dry it to form a surface - layer slurry layer 4; scrape a middle - layer slurry on the surface - layer slurry layer 4 and completely dry it to form a middle - layer slurry layer 5; scrape a bottom - layer slurry on the middle - layer slurry layer 5 and dry it to a semi - dry state to form a bottom - layer slurry layer 6; press a base layer 7 on the bottom - layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the base layer 7 is 1.20 mm; then dry, cool and shape, peel off the PET film, trim, and wind at a temperature of 110 °C with a vehicle speed of 6 m / min to obtain the first - process semi - finished product 100. The surface - layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping the surface - layer slurry on the nano - photonic crystal film, the number of coating rods is 15, and the coating amount is controlled at 160 g / m 2 ², the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the surface - layer slurry and completely volatilize the additives until there is no peculiar smell. The middle - layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping the middle - layer slurry on the surface - layer slurry layer 4, the number of coating rods is 18, and the coating amount is controlled at 190 g / m 2, the drying temperature is controlled at 90 °C and the drying time is 5 min to completely dry the middle layer slurry. The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 8000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥20.0, and the elongation at break is ≥500; when the bottom layer slurry is scraped on the middle layer slurry layer 5, the number of coating rods is 20, and the coating amount is controlled at 200 g / m 2 , the drying temperature is controlled at 100 °C and the drying air volume is 160 cm 3 / min for uniform blowing, the drying time is 10 s, and it is dried to a semi-dry state until a clear fingerprint can be formed by pressing with a finger, forming the bottom layer slurry layer 6 to obtain the first process semi-finished product 100.
[0068] Second process steps: Select the mirror release paper 8 as the second base material layer; scrape and dry the surface fabric slurry on the mirror release paper 8 to form the surface fabric slurry layer 1; scrape and dry the bottom layer slurry on the surface fabric slurry layer 1 to a semi-dry state to form the bottom layer slurry layer 2, obtaining the second process semi-finished product 200. The surface fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. The solid content of the polyurethane resin C is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥40.0, and the elongation at break is ≥650; when the surface fabric slurry is scraped on the mirror release paper 8, the number of coating rods is 15 filaments, and it is placed in an oven and dried at temperatures of 60 °C, 75 °C, 90 °C, 100 °C, 90 °C, 75 °C, and 60 °C, and the vehicle speed is set at 13 m / min. The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of cross-linking agent. The solid content of the polyurethane resin D is 70.0 ± 2.0%, the modulus is 4.0 ± 1.0, the breaking strength is ≥30.0, and the elongation at break is ≥500; when the bottom layer slurry is scraped on the surface fabric slurry layer 1, the number of coating rods is 18 filaments, the coating amount is controlled at 220 g / m2, the drying temperature is controlled at 100 °C, and the drying air volume is 160 cm 3 / min for uniform blowing, the drying time is 10 s, and it is dried to a nearly dry state until there are some fingerprint marks when pressed with a finger, forming the bottom layer slurry layer 2 to obtain the second process semi-finished product 200.
[0069] Laminating process steps: Use a laminating machine to laminate the bottom layer slurry layer 2 of the second process semi-finished product 200 with the nano-photonic crystal film of the first process semi-finished product 100; then perform drying, cooling and shaping, peeling off the mirror release paper 8, trimming, and winding to obtain the nano-photonic crystal synthetic leather. The oil stain adhesion amount of the nano-photonic crystal synthetic leather is ≤0.5 mg / cm 2 .
[0070] Example 2
[0071] A preparation process of an apparently rich green environmental protection nano - photonic crystal synthetic leather:
[0072] The first process step: Select a nano - photonic crystal film as the first substrate layer; scrape a surface layer slurry on the nano - photonic crystal film, and completely dry it to form a surface layer slurry layer 4; scrape a middle layer slurry on the surface layer slurry layer 4, and completely dry it to form a middle layer slurry layer 5; scrape a bottom layer slurry on the middle layer slurry layer 5, and dry it to a semi - dry state to form a bottom layer slurry layer 6; press a base layer 7 on the bottom layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the base layer 7 is 1.20 mm; then, at a temperature of 110 °C, dry, cool and shape, peel off the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain a semi - finished product 100 of the first process. The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping the surface layer slurry on the nano - photonic crystal film, the number of coating bars is 15, and the coating amount is controlled at 160 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell. The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping the middle layer slurry on the surface layer slurry layer 4, the number of coating bars is 18, and the coating amount is controlled at 190 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the middle layer slurry. The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 8000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500; when scraping the bottom layer slurry on the middle layer slurry layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 g / m 2 , the drying temperature is controlled at 100 °C, the drying air volume is 160 cm 3 / min and uniformly blow air, the drying time is 10 s, dry it to a semi - dry state, and it can form a clear fingerprint mark when pressed with a finger to form a bottom layer slurry layer 6, and obtain a semi - finished product 100 of the first process.
[0073] Second manufacturing step: Select the matte suede release paper 8 as the second base material layer; scrape and coat the fabric slurry on the matte suede release paper 8 and dry it to form the fabric slurry layer 1; scrape and coat the base slurry on the fabric slurry layer 1 and dry it to a semi-dry state to form the base slurry layer 2, obtaining the semi-finished product 200 of the second manufacturing process. The fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. The solid content of the polyurethane resin C is 30.0±1.0, the modulus is 70.0±2.0%, the breaking strength is ≥40.0, and the elongation at break is ≥650. When scraping and coating the fabric slurry on the matte suede release paper 8, the number of coating bars is 15 wires. Put it into the oven and dry it according to the temperatures of 60°C, 75°C, 90°C, 100°C, 90°C, 75°C, and 60°C. The vehicle speed is set at 13 m / min. The base slurry is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of cross-linking agent. The solid content of the polyurethane resin D is 70.0±2.0%, the modulus is 4.0±1.0, the breaking strength is ≥30.0, and the elongation at break is ≥500. When scraping and coating the base slurry on the fabric slurry layer 1, the number of coating bars is 18 wires, the coating amount is controlled at 220 g / m2, the drying temperature is controlled at 100°C, the drying air volume is 160 cm 3 / min and blow air uniformly. The drying time is 10 s. Dry it to a slightly dry state, and there should be some fingerprint marks when pressed with fingers to form the base slurry layer 2, obtaining the semi-finished product 200 of the second manufacturing process.
[0074] Laminating process step: Use a laminating machine to laminate the base slurry layer 2 of the semi-finished product 200 of the second manufacturing process with the nano-photonic crystal film of the semi-finished product 100 of the first manufacturing process; then carry out drying, cooling and shaping, peeling off the matte suede release paper 8, trimming, and winding to obtain the nano-photonic crystal synthetic leather. The oil stain adhesion amount of the nano-photonic crystal synthetic leather is ≤0.5 mg / cm 2 .
[0075] Comparative Example 1
[0076] A preparation process of synthetic leather:
[0077] The first manufacturing step: Select a common PVC film as the first base layer; scrape and coat a surface layer slurry on the common PVC film and completely dry it to form a surface layer slurry layer 4; scrape and coat a middle layer slurry on the surface layer slurry layer 4 and completely dry it to form a middle layer slurry layer 5; scrape and coat a bottom layer slurry on the middle layer slurry layer 5 and bake it to a semi-dry state to form a bottom layer slurry layer 6; press and bond a base layer 7 on the bottom layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the base layer 7 is 1.20 mm; then, at a temperature of 110 °C, dry, cool and shape, peel off the PET film, trim and wind up at a vehicle speed of 6 m / min to obtain a semi-finished product 100 of the first manufacturing process. The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When the surface layer slurry is scraped and coated on the common PVC film, the number of coating bars is 15, and the coating amount is controlled at 160 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell. The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When the middle layer slurry is scraped and coated on the surface layer slurry layer 4, the number of coating bars is 18, and the coating amount is controlled at 190 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the middle layer slurry. The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK and 10 parts of color powder, and the viscosity is controlled at 8000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500; when the bottom layer slurry is scraped and coated on the middle layer slurry layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 g / m 2 , the drying temperature is controlled at 100 °C, and the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 10 s to bake it to a semi-dry state, and a clear fingerprint can be formed by pressing it with a finger to form a bottom layer slurry layer 6, and a semi-finished product 100 of the first manufacturing process of traditional synthetic leather is obtained.
[0078] Second manufacturing step: Select the mirror release paper 8 as the second base layer; scrape and coat the fabric slurry on the mirror release paper 8 and dry it to form the fabric slurry layer 1; scrape and coat the base slurry on the fabric slurry layer 1 and dry it to a semi-dry state to form the base slurry layer 2, obtaining the semi-finished product 200 of the second manufacturing process. The fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. The solid content of the polyurethane resin C is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650; when scraping and coating the fabric slurry on the mirror release paper 8, the number of coating bars is 15 wires, and it is placed in an oven and dried at temperatures of 60 °C, 75 °C, 90 °C, 100 °C, 90 °C, 75 °C, and 60 °C, and the vehicle speed is set at 13 m / min. The base slurry is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of cross-linking agent. The solid content of the polyurethane resin D is 70.0 ± 2.0%, the modulus is 4.0 ± 1.0, the breaking strength is ≥ 30.0, and the elongation at break is ≥ 500; when scraping and coating the base slurry on the fabric slurry layer 1, the number of coating bars is 18 wires, the coating amount is controlled at 220 g / m2, the drying temperature is controlled at 100 °C, the drying air volume is 160 cm 3 / min and blow air evenly, the drying time is 10 s, and it is dried to a slightly dry state, and there are some fingerprint marks when pressed with a finger, forming the base slurry layer 2, the semi-finished product 200 of the second manufacturing process of traditional synthetic leather.
[0079] Laminating process step: Use a laminating machine to laminate the base slurry layer 2 of the semi-finished product 200 of the second manufacturing process of traditional synthetic leather with the ordinary PVC film of the semi-finished product 100 of the first manufacturing process of traditional synthetic leather; then perform drying, cooling and shaping, peeling the mirror release paper 8, trimming, and winding, obtaining traditional synthetic leather.
[0080] Product characteristics: The surface of the ordinary PVC film has no dense structure, and the oil stain adhesion amount of the synthetic leather is ≥ 2.0 mg / cm 2 。
[0081] Comparative Example 2
[0082] A preparation process of nano-photonic crystal synthetic leather:
[0083] The first manufacturing step: Select a nano - photonic crystal film as the first base layer; scrape and coat a surface layer slurry on the nano - photonic crystal film, and completely dry it to form a surface layer slurry layer 4; scrape and coat a middle layer slurry on the surface layer slurry layer 4, and completely dry it to form a middle layer slurry layer 5; scrape and coat a bottom layer slurry on the middle layer slurry layer 5, dry it to a semi - dry state to form a bottom layer slurry layer 6; press - fit a bass layer 7 on the bottom layer slurry layer 6 at a pressure of 0.5 MPa, and the thickness of the bass layer 7 is 1.20 mm; then, at a temperature of 110 °C, dry, cool and shape, peel the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain a semi - finished product 100 of the first manufacturing process. The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping and coating the surface layer slurry on the nano - photonic crystal film, the number of coating bars is 15, and the coating amount is controlled at 160 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell. The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping and coating the middle layer slurry on the surface layer slurry layer 4, the number of coating bars is 18, and the coating amount is controlled at 190 g / m 2 , the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the middle layer slurry. The bottom layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 8000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500; when scraping and coating the bottom layer slurry on the middle layer slurry layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 g / m 2 , the drying temperature is controlled at 100 °C, and the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 10 s to dry it to a semi - dry state, and a clear fingerprint can be formed when pressed with a finger to form the bottom layer slurry layer 6, and the semi - finished product 100 of the first manufacturing process is obtained. Directly use the semi - finished product 100 of the first manufacturing process as the finished product without performing the second manufacturing process and the re - laminating process.
[0084] Product features: The surface only presents the mirror plain structural color of the nano-photonic crystal film, without the texture effect given by the release paper; lacking the composite strengthening of the base paste layer and the fabric paste layer introduced by the laminating process; only relying on the stain resistance of the nano-film itself, with the oil stain adhesion amount ≤ 0.8 mg / cm 2 。
[0085] Comparative Example 3
[0086] A preparation process of nano-photonic crystal synthetic leather:
[0087] The first process step: Select a nano-photonic crystal film as the first base layer; scrape and coat a surface paste on the nano-photonic crystal film, and completely dry it to form a surface paste layer 4; scrape and coat a middle paste on the surface paste layer 4, and completely dry it to form a middle paste layer 5; scrape and coat a bottom paste on the middle paste layer 5, and dry it to a semi-dry state to form a bottom paste layer 6; press and laminate a base layer 7 on the bottom paste layer 6 at a pressure of 0.5 MPa, and the thickness of the base layer 7 is 1.20 mm; then at a temperature of 110 °C, dry, cool and shape, peel off the PET film, trim, and wind up at a vehicle speed of 6 m / min to obtain a semi-finished product 100 of the first process. The surface paste is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping and coating the surface paste on the nano-photonic crystal film, the number of coating bars is 15, and the coating amount is controlled at 160 g / m 2 ², the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the surface paste and completely volatilize the additives until there is no peculiar smell. The middle paste is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 2800 CPS; the solid content of the polyurethane resin A is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650. When scraping and coating the middle paste on the surface paste layer 4, the number of coating bars is 18, and the coating amount is controlled at 190 g / m 2 ², the drying temperature is controlled at 90 °C, and the drying time is 5 min to completely dry the middle paste. The bottom paste is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 10 parts of color powder, and the viscosity is controlled at 8000 CPS; the solid content of the polyurethane resin B is 40.0 ± 1.0, the modulus is 30.0 ± 2.0%, the breaking strength is ≥ 20.0, and the elongation at break is ≥ 500; when scraping and coating the bottom paste on the middle paste layer 5, the number of coating bars is 20, and the coating amount is controlled at 200 g / m 2 ², the drying temperature is controlled at 100 °C, and the drying air volume is 160 cm3 Blow air evenly at [X] / min, with a drying time of 10 s until it is semi-dry. It is okay if clear fingerprint marks are formed when pressed with a finger, thus forming the bottom layer slurry layer 6.
[0088] Second manufacturing process step: Select a common PET film as the second base layer; scrape and coat fabric slurry on the common PET film and dry it to form the fabric slurry layer 1; scrape and coat base slurry on the fabric slurry layer 1 and dry it to a semi-dry state to form the base slurry layer 2, obtaining the semi-finished product 200 of the second manufacturing process. The fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. The solid content of the polyurethane resin C is 30.0 ± 1.0, the modulus is 70.0 ± 2.0%, the breaking strength is ≥ 40.0, and the elongation at break is ≥ 650; when scraping and coating the fabric slurry on the common PET film, the number of coating bars is 15 wires. Put it into the oven and dry it at the temperatures of 60°C, 75°C, 90°C, 100°C, 90°C, 75°C, and 60°C, and set the vehicle speed to 13 m / min. The base slurry is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of cross-linking agent. The solid content of the polyurethane resin D is 70.0 ± 2.0%, the modulus is 4.0 ± 1.0, the breaking strength is ≥ 30.0, and the elongation at break is ≥ 500; when scraping and coating the base slurry on the fabric slurry layer 1, the number of coating bars is 18 wires, the coating amount is controlled at 220 g / m2, the drying temperature is controlled at 100°C, and the drying air volume is 160 cm 3 / min blow air evenly, with a drying time of 10 s until it is nearly dry. It is okay if there are some fingerprint marks when pressed with a finger, thus forming the base slurry layer 2.
[0089] Laminating process step: Use a laminating machine to laminate the base slurry layer 2 of the semi-finished product 200 of the second manufacturing process with the nano-photonic crystal film of the semi-finished product 100 of the first manufacturing process; then carry out drying, cooling and shaping, peeling off the PET film, trimming, and winding, obtaining the nano-photonic crystal synthetic leather.
[0090] Product characteristics: Since the PET film has no texture design on the surface, only the optical effect of the nano-photonic crystal film is retained, without mirror / matte velvet texture; the insufficient surface smoothness of the PET film leads to an increase in stain residue, and the oil adhesion amount ≤ 1.2 mg / cm 2 .
[0091] Table 1 Comparison table of performance indicators of each example and comparative example
[0092]
[0093]
[0094] (Note: ΔE was tested using a spectrophotometer; glossiness was tested according to ISO 2813; Taber abrasion resistance test was carried out using an H22 grinding wheel; peel strength was tested according to ASTM D903 standard)
[0095] Conclusion:
[0096] 1. In Examples 1 and 2, significant angle-dependent color change (ΔE≥15) was achieved through the physical structural color of the nano-photonic crystal film, far exceeding that of the traditional ordinary PVC film in Comparative Example 1 (ΔE≤2); although structural color was retained in Comparative Examples 2 and 3, the lack of texture superposition in the lamination process or insufficient light transmittance of the PET film led to a single optical level.
[0097] 2. The lamination process in Examples 1 and 2 combined the texture of the release paper (mirror / matte) with the structural color to achieve ≥5 texture effects. In Comparative Examples 1, 2, and 3, due to process simplification or material substitution, the appearance was single (≤2 textures or no superposition effect).
[0098] 3. The mirror glossiness of Examples 1 and 2 was ≥90GU, and the matte glossiness was 20 - 30GU, meeting the requirements of the high-end fashion field. The substitution of the PET film for the release paper in Comparative Example 3 led to a decrease in glossiness (85 - 88GU), resulting in poor optical performance.
[0099] 4. The nano-photonic crystal film + lamination process in Examples 1 and 2 synergistically improved the abrasion resistance of the synthetic leather (Taber 2000 rotations, Stoll 800 - 1000 times). The abrasion resistance of Comparative Example 1 was the lowest (Taber 150 rotations, Stoll 400 times), and the chemical coating was easily worn.
[0100] 5. The lamination process in Examples 1 and 2 optimized the bonding interface, and the peel strength was ≥132N / 3cm, with the best bonding stability. The use of an ordinary PET film in Comparative Example 3 had weak adhesion, and the peel strength was reduced to 110N / 3cm.
[0101] Therefore, the preparation process of a nano-photonic crystal synthetic leather according to the present invention works synergistically through three steps: the first process, the second process, and the lamination process; the first process provides basic optical properties, abrasion resistance, and stain resistance, endowing the synthetic leather with core functions; the second process introduces diverse surface textures through different release papers (mirror / matte) to enrich the appearance level; the lamination process combines the optical properties of the first process with the textures of the second process to achieve the composite effect of "physical structural color + texture design", making the nano-photonic crystal synthetic leather have the advantages of diverse appearance effects achieved by the superposition of structural color and texture, environmental friendliness, and significant improvement in abrasion resistance and peel strength.
[0102] Although the specific embodiments of the present invention have been described above, those skilled in the art should understand that the specific embodiments we described are illustrative rather than used to limit the scope of the present invention. Equivalent modifications and variations made by those skilled in the art in accordance with the spirit of the present invention should be covered by the scope protected by the claims of the present invention.
Claims
1. A preparation process of an apparent rich green environmental protection nano - photonic crystal synthetic leather, characterized in that: It includes a first manufacturing process step: selecting a nano-photonic crystal film as the first base layer; scraping and coating a surface layer slurry on the nano-photonic crystal film and completely drying it to form a surface layer slurry layer; scraping and coating a middle layer slurry on the surface layer slurry layer and completely drying it to form a middle layer slurry layer; scraping and coating a bottom layer slurry on the middle layer slurry layer and drying it to a semi-dry state to form a bottom layer slurry layer; laminating a base layer on the bottom layer slurry layer; and then drying, cooling, peeling, trimming, and winding to obtain a semi-finished product of the first manufacturing process.
2. The preparation process of the apparently rich green environmental protection nano-photonic crystal synthetic leather according to claim 1, characterized in that: The surface layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of color powder, and the viscosity is controlled at 2700 - 3000 CPS; when the surface layer slurry is scrape-coated on the nano-photonic crystal film, the number of coating bars is 15, and the coating amount is controlled at 150 - 160 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the surface layer slurry and completely volatilize the additives until there is no peculiar smell; The middle layer slurry is prepared by uniformly mixing 100 parts of polyurethane resin A, 60 parts of DMF, 20 parts of MEK, and 4 - 15 parts of toner, and the viscosity is controlled at 2700 - 3000 CPS; when the middle layer slurry is scrape-coated on the surface layer slurry layer, the number of coating bars is 18, and the coating amount is controlled at 180 - 190 g / m 2 , the drying temperature is controlled at 90 - 100 °C, and the drying time is 4 - 5 min to completely dry the middle layer slurry; The underlying slurry is prepared by uniformly mixing 100 parts of polyurethane resin B, 20 parts of DMF, 20 parts of MEK, and 4 - 15 parts of toner, and the viscosity is controlled at 8000 - 10000 CPS; when the underlying slurry is scrape-coated on the middle slurry layer, the number of coating bars is 20, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, the drying air volume is 160 cm 3 / min for uniform blowing, and the drying time is 7 - 10 s until it is semi-dry, and a clear fingerprint can be formed when pressed with a finger to form the underlying slurry layer.
3. The preparation process of the apparently rich green and environment-friendly nano-photonic crystal synthetic leather according to claim 1, characterized in that: The thickness of the base layer is 1.15 - 1.25 mm.
4. The preparation process of the apparently rich green environmental protection nano-photonic crystal synthetic leather according to claim 1, characterized in that: A PET layer is adhered to the side of the nano-photonic crystal film away from the surface layer slurry layer. When scraping and coating the surface layer slurry, the PET layer serves as a carrier for the nano-photonic crystal film, and the PET layer is peeled off from the nano-photonic crystal film during the peeling step.
5. The preparation process of the apparently rich green environmental protection nano-photonic crystal synthetic leather according to any one of claims 1-3, characterized in that: It further includes a second manufacturing process step: selecting a release paper as the second base layer; scraping and coating a fabric slurry on the release paper and drying it to form a fabric slurry layer; scraping and coating a bottom layer slurry on the fabric slurry layer and drying it to a semi-dry state to form a bottom layer slurry layer, thereby obtaining a semi-finished product of the second manufacturing process.
6. The preparation process of the apparently rich green environmental protection nano-photonic crystal synthetic leather according to claim 5, characterized in that: The fabric slurry is prepared by uniformly mixing 100 parts of polyurethane resin C, 60 parts of DMF, and 20 parts of MEK. When scraping and coating the fabric slurry on the release paper, the number of coating bars is 15 wires. It is placed in an oven and dried at temperatures of 60°C, 75°C, 90°C, 100°C, 90°C, 75°C, and 60°C, and the vehicle speed is set at 13 m / min. The base paste is prepared by uniformly mixing 100 parts of polyurethane resin D, 10 parts of DMF, 5 parts of MEK, and 5 parts of crosslinking agent. When the base paste is scrape-coated on the fabric paste layer, the number of coating bars is 18 filaments, and the coating amount is controlled at 200 - 220 g / m 2 , the drying temperature is controlled at 100 - 110 °C, the drying air volume is 160 cm 3 / min for uniform blowing, the drying time is 7 - 10 s, dried to a semi-dry state, with a little fingerprint mark when pressed by finger, forming the base paste layer.
7. The preparation process of the apparent rich green environmental protection nano - photonic crystal synthetic leather according to claim 5, characterized in that: The release paper serves as a carrier for the fabric slurry layer, and the release paper is any one of a mirror release paper or a matte suede release paper.
8. The preparation process of the apparently rich green and environmentally friendly nano-photonic crystal synthetic leather according to any one of claims 6-7, characterized in that: It further includes a re-laminating process step: using a laminating machine to perform a face-laminating operation on the bottom layer slurry layer of the semi-finished product of the second manufacturing process and the nano-photonic crystal film of the semi-finished product of the first manufacturing process; and then drying, cooling and shaping, peeling off the release paper, trimming, and winding to obtain a nano-photonic crystal synthetic leather.
9. The preparation process of the apparently rich green environmental protection nano-photonic crystal synthetic leather according to claim 8, characterized in that: First, apply a layer of water above the nano-photonic crystal film, and then perform a face-laminating operation with the bottom layer slurry layer; the drying in the re-laminating process step is carried out at a temperature of 140°C with a vehicle speed of 6 m / min, and the drying duration is 7 - 10 min.
10. The preparation process of the apparent rich green environmental protection nano-photonic crystal synthetic leather as described in claim 8, characterized in that: The nano-photonic crystal synthetic leather sequentially includes a fabric slurry layer, a bottom layer slurry layer, a nano-photonic crystal film layer, a surface layer slurry layer, a middle layer slurry layer, a bottom layer slurry layer, and a base layer from top to bottom.